2003
DOI: 10.1161/01.atv.0000044461.01844.c9
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Ligands Increase Release of Nitric Oxide From Endothelial Cells

Abstract: Objective-Peroxisome proliferator-activated receptor ␥ (PPAR␥) ligands reduce lesion formation in animal models of atherosclerosis by mechanisms that have not been defined completely. We hypothesized that PPAR␥ ligands stimulate endothelial-derived nitric oxide release (·NO) to protect the vascular wall. Methods and Results-The PPAR␥ ligands, 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) or ciglitazone, stimulated a PPAR response element-luciferase reporter construct in transfected porcine pulmonary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
2
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(185 citation statements)
references
References 49 publications
9
158
2
10
Order By: Relevance
“…We chose to use PAE cells because they are deficient in endogenous EGFR. TGZ (25-50 mM, 24 h incubation) activated PPARγ with a typical 2-3-fold increase in PPRE luciferase reporter activity ( Figure 1A), in good agreement with previous reports [27], while EGF failed to cross-activate the PPRE reporter. TGZ stimulation resulted in rapid Erk1/2 phosphorylation in PAE-EGFR cells, but not in PAE cells ( Figure 1B), suggesting that TGZ could elicit signaling through EGFR.…”
Section: Troglitazone Activated Egfr Signaling Independent Of Pparγsupporting
confidence: 92%
“…We chose to use PAE cells because they are deficient in endogenous EGFR. TGZ (25-50 mM, 24 h incubation) activated PPARγ with a typical 2-3-fold increase in PPRE luciferase reporter activity ( Figure 1A), in good agreement with previous reports [27], while EGF failed to cross-activate the PPRE reporter. TGZ stimulation resulted in rapid Erk1/2 phosphorylation in PAE-EGFR cells, but not in PAE cells ( Figure 1B), suggesting that TGZ could elicit signaling through EGFR.…”
Section: Troglitazone Activated Egfr Signaling Independent Of Pparγsupporting
confidence: 92%
“…In endothelial cell culture troglitazone treatment resulted in a parallel fall in expression of adhesion molecules and NF B [22]. This fall may be due to increased NO levels and PPAR␥ ligands increase NO release in vitro but do not increase eNOS expression or protein levels [23]. Pioglita-zone is an insulin sensitizer but the direct effect of insulin on adhesion molecules is uncertain.…”
Section: Discussionmentioning
confidence: 98%
“…In the mouse, in contrast to the rat, Pio caused a small, yet significant, increase in eNOS phosphorylation at both Ser633 and Ser1177, suggesting the activation by protein kinase A (and/or other kinases) (26). Other studies have suggested that PPAR␥ agonists increase NO production by eNOS without affecting the total eNOS expression (10,28,47). Hwang et al (28) reported that ciglitazone increases the bioavailability of NO by an increased expression of Cu/Zn-superoxide dismutase and a suppression of NADPH oxidase.…”
Section: Role Of Enosmentioning
confidence: 95%